The Pioneer Transcription Factor Foxa2 Modulates T Helper Differentiation to Reduce Mouse Allergic Airway Disease - Yánez, Diana C.; Lau, Ching-In; Papaioannou, Eleftheria; Chawda, Mira M.; Rowell, Jasmine; Ross, Susan; Furmanski, Anna; Crompton, Tessa (Frontiers in Immunology, 2022)
Foxa2, a member of the Forkhead box (Fox) family of transcription factors, plays an important role in the regulation of lung function and lung tissue homeostasis. Foxa2 expression is reduced in the lung and airways epithelium of asthmatic patients and in mice absence of Foxa2 from the lung epithelium contributes to airway inflammation and goblet cell hyperplasia. Here we demonstrate a novel role for Foxa2 in the regulation of T helper differentiation and investigate its impact on lung inflammation. Conditional deletion of Foxa2 from T-cells led to increased Th2 cytokine secretion and differentiation, but decreased Th1 differentiation and INF- expression in vitro. Induction of mouse allergic airway disease resulted in more severe disease in the conditional Foxa2 knockout than in control mice, with increased cellular infiltration to the lung, characterized by the recruitment of eosinophils, mast cells and basophils, increased mucus production and increased production of Th2 cytokines. Thus, these experiments suggest that Foxa2 expression in T-cells is required to protect against the Th2 inflammatory response in allergic airway inflammation and that Foxa2 is important in T-cells to maintain the balance of effector cell differentiation and function in the lung.